Aprotinin and transfusion requirements in pediatric craniofacial surgery. Issue 2 (18th October 2013) - Ahmed, Zulfiqar; Stricker, Lori; Rozzelle, Arlene; Zestos, Maria; Davidson, Andrew
Summary Objective To evaluate transfusion requirements in children receiving aprotinin during craniofacial surgery. Background Pediatric craniofacial procedures may involve massive blood loss. Aprotinin may decrease perioperative blood loss and transfusion requirements. Methods Patients (aged 1 month to 3 years) who had major reconstructive craniofacial surgery received intraoperative aprotinin (13 patients) or placebo (13 patients). Administered colloids and blood products were recorded. Results Patients in the aprotinin and placebo groups had similar mean age, body weight, body surface area, operative time, and length of hospital stay. Mean volumes of total colloids (aprotinin group: 70 ± 40 ml; and placebo group: 120 ± 80 ml; P ≤ 0.05) and packed red blood cells (aprotinin group: 380 ± 90 ml; and placebo group: 550 ± 200 ml; P ≤ 0.004) were less in the aprotinin group than in the placebo group. Mean urine output during surgery was greater in the aprotinin group than in the placebo group (320 ± 200 ml vs 150 ± 70 ml, respectively; P ≤ 0.003). Mean blood urea nitrogen and serum creatinine values after surgery were similar between the groups. Complications of aprotinin included anaphylaxis (one patient) and rash (one patient); no deaths occurred. Conclusions Aprotinin was associated with decreased packed red blood cell transfusion requirements in children undergoing craniofacial surgery, with no renal toxicity or death. Aprotinin is no longer available for clinical use in the USA because of adverse effects in adults; re‐evaluation of aprotinin is warranted for children scheduled to undergo surgery involving potentially high blood loss.